Building iPhone and iPad electronic projects - Westerfield, Mike (O'Reilly, 2013)
Why simply play music or go online when you can use your iPhone or iPad for some really fun projects, such as building a metal detector, hacking a radio control truck, or tracking a model rocket in flight? Learn how to build these and other cool things by using iOS device sensors and inexpensive hardware such as Arduino and a Bluetooth Low Energy (LE) Shield. This hands-on book shows you how to write simple applications with techBASIC, an Apple-approved development environment that runs on iOS devices. By using code and example programs built into techBASIC, you'll learn how to write apps directly on your Apple device and have it interact with other hardware. Build a metal detector with the iOS magnetometer Use the HiJack hardware platform to create a plant moisture sensor Put your iPhone on a small rocket to collect acceleration and rotation data Hack a radio control truck with Arduino and Bluetooth LE Create an arcade game with an iPad controller and two iPhone paddles Control a candy machine with an iOS device, a micro servo, and a WiFi connection.